Clinical Diagnosis and Management Challenges of Harlequin Ichthyosis in a Preterm Neonate: A Case Report From Uganda - Munanura Turyasiima; Djamila Magan Mohamed; Hamdi Mohamed Yusuf; Gloria Nakalema; Balbina Gillian Akot; Joan Kyoshabire; Shabirih Mutagamba; Grace Gladys Kimono; Jimmy Emmy Duca; Ibrahimu Makongwa (Case Reports in Dermatological Medicine)
Conclusion: Harlequin ichthyosis remains associated with a high mortality rate, especially in resource-limited settings. Contributing factors include inadequate prenatal diagnostic services, restricted access to essential treatments, and insufficient neonatal care infrastructure, all of which exacerbate poor outcomes in developing countries.